Phylogeographic Insights of Five Co-Habiting Grouper Species in The Indo-Malaya Archipelago - Nur Fadli; Adrian Damora; Zainal A. Muchlisin; Irma Dewiyanti; Mutia Ramadhaniaty; Nanda Muhammad Razi; Jamsari Amirul Firdaus Jamaluddin; Edison D. Macusi; Mohd Nor Siti-Azizah (HAYATI Journal of Biosciences, 2023)
Understanding the patterns of genetic diversity of species and precise stock identification are important in fisheries conservation management. However, studies on genetic diversity, connectivity, population structure, and gene flow of groupers within the Indo-Malaya Archipelago (IMA) waters are limited. The objective of the present study was to examine the phylogeographic patterns of the family Epinephelidae in IMA waters based on a parallel study of five selected species utilizing the mitochondrial COI. The grouper species were: areolate grouper (Epinephelus areolatus), blacktip grouper (Epinephelus fasciatus), six-bar grouper (Epinephelus sexfasciatus), blue-lined hind (Cephalopholis formosa), and white-edged lyretail (Variola albimarginata). Specimens were obtained from fish landing sites and fish markets from 23 locations throughout the IMA waters. This study showed genetic structuring for two species (Epinephelus areolatus and Variola albimarginata) but genetic homogeneity for the other three investigated species across IMA. Various geological and demographic histories, local and regional oceanographic features, and biological characteristics are hypothesized to shape the present genetic pattern of each species across the IMA waters. The establishment of effective international cooperation is encouraged to manage grouper species stocks in this region.